Exploring Teachers Power’s Verbal Symbolic in a Classroom Interaction; A Pragmahypersemiotics Study - Mardiningsih, Mardiningsih; Laksono, Kisyani; Yohanes, Budinuryanta (International Journal of Language Education, 2023)
This qualitative study investigated the verbal use of teacher symbols in a classroom Indonesian at a private university in Surabaya, Indonesia. Anchored by qualitative analysis and followed by two female teachers and five Indonesian Department students, the data was collected through interviews and in-depth observation. It was designed to find out what types of pragmahypersemiotic verbal symbols teachers use in the classroom, as well as the extent to which pragmahypersemiotic verbal symbols contribute to student feedback in class. Using the analytical lens of verbal symbol power in the classroom, the research findings show that the type of verbal power teacher symbol used in the classroom is the symbol of Directive, Request, and enticement. However, verbal symbols can have a positive impact on student feedback because students can participate actively in class, and can build motivation and confidence when interacting with both teachers and classmates.